Idola kimia : sari pati pilihan terlengkap kimia SMP kelas VII, VIII, IX /Rizky Oktariani, Ernawati ; penyunting, Chrisna Farmadiani - RIZKY OKTARIANI, 1987-; Ernawati; Chrisna Farmadiani (Trans Idea Publishing, 2013)
196 hlm. : ilus. ; 19 cm.